Fundamentals of food biotechnology - Lee, B. H. (Byong H.) (Chichester, West Sussex, UK : Wiley Blackwell, 2015)
Food biotechnology is the application of modern biotechnological techniques to the manufacture and processing of food, for example through fermentation of food (which is the oldest biotechnological process) and food additives, as well as plant and animal cell cultures. New developments in fermentation and enzyme technological processes, molecular thermodynamics, genetic engineering, protein engineering, metabolic engineering, bioengineering, and processes involving monoclonal antibodies, nanobiotechnology and quorum sensing have introduced exciting new dimensions to food biotechnology, a burg.
2.1 Concepts of macromolecules: function and synthesis2.1.1 DNA replication; 2.1.2 Roles of RNA; 2.1.3 Detailed aspects of protein synthesis; 2.2 Concepts of recombinant DNA technology; 2.2.1 Restriction endonucleases; 2.2.2 Plasmid vectors; 2.2.3 Purpose of gene cloning; 2.3 DNA sequencing; 2.4 Polymerase chain reaction (PCR); 2.5 Manipulation techniques of DNA; 2.5.1 Isolation and purification of nucleic acids; 2.5.2 Agarose gel electrophoresis; 2.5.3 Blotting and hybridization; 2.6 Gene cloning and production of recombinant proteins.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Food -- Biotechnology; Agricultural biotechnology; Food -- Biotechnology; TECHNOLOGY & ENGINEERING -- Food Science; Food -- Biotechnology; Electronic books